Analisis Perbedaan Motivasi Belajar antara Mahasiswa yang Tinggal di Kos Dengan Mahasiswa yang Tinggal Bersama Orangtua di Kelas B Semester VI Program Studi PBSI - Laowo, Darni Marsellin; Hura, Delfita; Waruwu, Fajar Iman; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
This study is based on the difference in motivation when comparing the learning motivation of students who live in boarding houses with students who live with their parents, students who live with their parents have higher learning motivation compared to the learning motivation of living in boarding houses. This study aims to distinguish the motivation of students who live in boarding houses and students who live with their parents. This study uses a qualitative research method with a descriptive approach. The subjects used in this study are students from the University of Nias. The object of this research is student learning motivation. The data collection technique uses interviews and observations to students in the classroom. Primary data were obtained through observation and interviews, focusing on factors that affect learning motivation, such as independence, social support, and personal goals. Data analysis techniques use reduction, data presentation, and data verification.  The results showed significant differences in learning motivation between the two groups of students, which was driven by the context of their living environment. This research highlights the importance of these factors in supporting the student learning process in higher education.